KONTRIBUSI USAHATANI MADU SIALANG TERHADAP PENDAPATAN KELUARGA PETANI (Studi Kasus Di Desa Gunung Sahilan Kecamatan Gunung Sahilan Kabupaten Kampar) - Ridha Maulana M; Eriyati '; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the Village of Gunung Sahilan District of Gunung Sahilan Kampar regency. The purpose of this study was to determine the contribution of honey bee beehive farm to the family income of farmers in the Village of Gunung Sahilan District of Gunung Sahilan Kampar regency. This study uses a sampling technique saturated (census) saturated sampling technique (census) is the sampling technique when the number of relatively small population, less than 30 people, in which all members of the population sampled. 27 samples were selected. The analytical method used in this research is quantitative descriptive method by describing the whole object of research with the number and percentage into the later described sentence description. The results showed that farm Honey beehive has contributed to the family income of farmers. The results showed that farm Honey beehive is the livelihood of a side which has a contribution of 75% of more than half of livelihood principal contributed by 15% as farming oil palm, rubber farming and a 10% contribution comes from donations income than farming honey beehive nonagricultural.Keywords: Income, Total Tree, Total Nest, Capital.